2008
DOI: 10.1002/bjs.6107
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal lavage cytology in patients with oesophagogastric adenocarcinoma

Abstract: Background: The aim of the study was to determine the value of performing peritoneal lavage cytology during laparoscopy in the management of oesophagogastric adenocarcinoma.Methods: Laparoscopy combined with peritoneal cytology was performed in patients with potentially resectable oesophagogastric adenocarcinoma. Macroscopic peritoneal findings at laparoscopy and the presence of free peritoneal tumour cells were recorded. All patients were followed to death or the census point. Patients with overt peritoneal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 31 publications
(12 reference statements)
2
34
0
3
Order By: Relevance
“…However, the rate of 4.59% in our study is similar to another study also using laparoscopy to obtain cytological samples. 25 The small numbers of patients with positive peritoneal cytology alone in this study make it difficult to make any definite conclusions. Nevertheless, there does not appear to be a significant difference in survival in patients with macroscopic peritoneal disease compared with those with positive peritoneal cytology.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the rate of 4.59% in our study is similar to another study also using laparoscopy to obtain cytological samples. 25 The small numbers of patients with positive peritoneal cytology alone in this study make it difficult to make any definite conclusions. Nevertheless, there does not appear to be a significant difference in survival in patients with macroscopic peritoneal disease compared with those with positive peritoneal cytology.…”
Section: Resultsmentioning
confidence: 83%
“…This supports the findings of previous research and would suggest that treatment with curative intent ought not to be attempted in patients with positive peritoneal cytology. 25 The best form of palliation for these patients remains undetermined. Despite the apparent value of staging laparoscopy in identifying incurable disease, there appears to be considerable variability in its use.…”
Section: Resultsmentioning
confidence: 99%
“…Cytology is easy and safe to perform, it takes approximately 15 min for a cytopathologist to analyze the patient's slides, and the estimated cost for this procedure is $ 60 20 . The rate of detection of IFCC in the literature ranges from 14%-47%, depending upon the cohort of patients studied 21 . When only potentially curative resections are included, the rate of IFCC varies from 4.4%-11%, and ranges from 22%-30% in gastric carcinoma involving the serosa [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…Most of these patients have a poor prognosis, with a substantially high risk for peritoneal recurrence, even in the absence of overt peritoneal carcinomatosis [3,17,[19][20][21][22][23][24]. Nath et al demonstrated no significant difference in median survival between patients with only positive malignant cytology (13 months) versus those with macroscopic peritoneal disease (9 months) [25]. In the study by Bando et al, all 296 patients (24 % of cohort) with positive peritoneal cytology died within 3 years despite radical tumor resection [19].…”
Section: Discussionmentioning
confidence: 99%